NOVICE BIPA TEACHING PRACTITIONERS' PERCEPTIONS OF VIOLATIONS OF THE COOPERATIVE PRINCIPLE IN VIRTUAL CLASSROOM INTERACTION A QUALITATIVE CASE STUDY - Dewi, Herliana; Yustika Nur Fajriah; Setia Muljanto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research investigates the perceptions of beginner BIPA (Bahasa Indonesia for Foreign Speakers) teaching practitioners regarding violations of the Cooperative Principle in online classroom interactions. Although earlier research has mainly concentrated on pinpointing and categorizing maxim breaches in classroom discussions, there has been little emphasis on how new practitioners view and react to these communication challenges in BIPA settings. This qualitative case study focused on two beginner BIPA teaching practitioners who had finished virtual teaching practice sessions. Data were gathered via semi-structured interviews and examined employing thematic analysis. The results indicated that participants viewed successful classroom communication as a collective duty of both educators and students. Breach of conversational norms were typically seen as inherent aspects of novice language acquisition instead of deliberate lack of collaboration. Participants identified communication challenges primarily due to learners' restricted vocabulary, inadequate language skills, low self-confidence, and partial comprehension of the instructional material. To tackle these issues, professionals used clarification, repetition, simplified descriptions, contextual illustrations, visual aids, and corrective feedback. The research emphasizes the significance of educators' views in fostering communication and student growth in online BIPA classrooms.